Damage control surgery for spontaneous perforation of pyometra with septic shock: a case report. Issue 1 (19th May 2021) - Matsumoto, Ryo; Kuramoto, Shunsuke; Muronoi, Tomohiro; Oka, Kazuyuki; Shimojyo, Yoshihide; Kidani, Akihiko; Hira, Eiji; Watanabe, Hiroaki
Abstract : Background: Although spontaneous perforation of pyometra is very rare, it sometimes causes severe peritonitis, leading to lethal conditions. Damage control surgery reportedly improves the survival of critically ill patients; however, there has been no report describing damage control surgery for ruptured pyometra. Case presentation: An 83‐year‐old postmenopausal woman with generalized peritonitis and septic shock was admitted and underwent emergency laparotomy. Abbreviated surgery was carried out because of progressing septic shock, and planned reoperation was carried out 2 days after the initial surgery. Histopathological examination revealed the perforation of pyometra with no evidence of malignancy. The patient was discharged on the 32nd postoperative day in stable condition. Conclusion: We report a case of spontaneous perforation of pyometra with severe septic shock successfully treated by damage control surgery. Damage control surgery is a useful treatment option for hemodynamically unstable patients with diseases in the field of obstetrics and gynecology. Abstract : We experienced a case of spontaneous perforation of pyometra successfully treated by damage control surgery. Acute care surgeons should consider damage control surgery as a useful treatment option for spontaneously ruptured pyometra in severe peritonitis.